Grid Forming Converters for Low Inertia Systems-Capabilities and Limitations: A Critical Review - Qusay Salem; Bayan Bany Fawaz; Rafat Aljarrah; Mazaher Karimi (IEEE Open Journal of the Industrial Electronics Society)
The rapid integration of renewable energy sources into the power grid has resulted in the high utilization of power-electronics devices and operating power systems where inverter-based resources are dominated. Such a transition has led to a reduction of inertia and system strength. In recent research, grid-forming converters (GFM) are introduced and developed to alleviate the grid-following converter (GFL) functionalities and to address the limitations concerning grid support capability, stability, and synchronization issues. However, the efficacy of GFM technology is still under investigation, and the level at which GFM converters can replace traditional GFLs is still under question. This article aims to bridge the gap in literature by revisiting the up-to-date research on the capabilities and the limitations of the proposed GFM converters compared to the traditionally utilized GFL converters, allowing a better understanding of the current status and future requirements. This includes the GFM converter's topologies and their performance for small- and large-signal stability issues, the GFM converters' ability to enhance grid synchronization, and transient stability performances. Furthermore, the challenges and limitations of the dynamic behavior of GFM converters from the point of view of fault ride through (FRT) capability, including grid codes and FRT requirements, FRT methods of GFM converters, postfault behavior, and open research directions, are also comprehensively reviewed. Finally, this article has been concluded by highlighting the main findings, considerations, and future recommendations.